ANALISIS KANDUNGAN LOGAM BERAT (Pb, Cd, DAN Cu) PADA LAMUN (Enhalus acoroides DAN Thalassia Hemprichii) SEBAGAI BIOINDIKATOR PENCEMARAN DI TELUK BALIKPAPAN, KOTA BALIKAPAPAN, KALIMANTAN TIMUR - Mahesa Islamy Eka Juniar; Jailani Jailani; Ghitarina Ghitarina (Jurnal Tropical Aquatic Sciences, 2022)
There are many activities in and around Balikpapan Bay which is expected to provide input of organic matter and waste containing heavy metals that may accumulate in seagrass. Seagrass is a material that can be used for analysis of heavy metal content and can accumulate these contaminants. This study aimed to analyze the levels of heavy metals (Pb, Cd, and Cu) in seagrass (Enhalus acoroides and Thalassia hemprichii) in the waters of Balikpapan Bay. Seagrass samples were taken at two stations with three repetitions. The samples were then dry-destructed prior to heavy metal analysis. Analyses The results showed that the heavy metal content of Pb was higher at Station 2 (dominated by Thalassia hemprichii) in the stem, Cd was higher at Station 1 (dominated by Enhalus acoroides) in the stem, and Cu was found higher on the leaf. Of the Seagrass at Station 2. The levels of Pb in the seagrass have exceeded the quality standard stipulated in KEPMEN No. 51 of 2004.